2008
DOI: 10.3945/jn.108.089482
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Protein Tyrosine Phosphatase 1B by Manipulation of Dietary Selenium Affects the Triglyceride Concentration in Rat Liver

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a key enzyme in the counter-regulation of insulin signaling and in the stimulation of fatty acid synthesis. Selenium (Se), via the activities of glutathione peroxidase (GPx) and thioredoxin reductase (TrxR), is involved in the removal of H(2)O(2) and organic peroxides, which are critical compounds in the modulation of PTP1B activity via glutathionylation. Our study with growing rats investigated how the manipulation of dietary Se concentration influences the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 85 publications
6
41
0
Order By: Relevance
“…Glutathione from GPx activity has also been shown to regulate PTP1B activity (45). We observed an increase in GPx1 mRNA levels in the liver of Scly KO mice fed an adequate-Se diet (Table 2), but such increase was not accompanied by its protein levels (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Glutathione from GPx activity has also been shown to regulate PTP1B activity (45). We observed an increase in GPx1 mRNA levels in the liver of Scly KO mice fed an adequate-Se diet (Table 2), but such increase was not accompanied by its protein levels (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…More specifically, the Se-overdosed pigs had >50% plasma insulin levels than the Se-adequate pigs to maintain similar plasma glucose concentrations, indicating an early sign of insulin resistance. Unlike rats [58][59][60], pigs fed the high-Se diet (3 mg of Se/kg of diet) did not develop hyperlipidemia compared with those fed 0.3 mg of Se/kg of diet. Meanwhile, Pinto et al [63] reported that after 16 weeks of intervention, fasting plasma insulin and cholesterol levels were increased in pigs fed 0.50 mg of Se/kg of diet (as Se-yeast) compared with those fed 0.17 mg of Se/kg of diet, although fasting glucose concentrations did not differ between the two groups.…”
Section: Elevations Of Se Intake and Selenoprotein Expression On Diabmentioning
confidence: 99%
“…First, many of the past animal studies used diabetic animals [29][30][31][32][33][34][35][36][37][38][39], but the present studies have been conducted in normal animals [53,[57][58][59][60][62][63]. Second, the past experiments used high or nearly toxic doses of Se (0.9-4.5 mg/kg body weight) [29][30][31][32][33][34][35][36][37][38][39], while recent experiments used Se levels not exceeding their maximal tolerable limits (≤33.0 mg Se/kg diet).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats that were fed 75 or 150 μg of selenium/kg showed an increase in thioredoxin reductase, as well as other selenoproteins, and a decrease in PTP1B glutathionylation (which inhibits PTP activity). 285 It is possible that the oxidation of PTPs via the oxidative stress of tamoxifen treatment can play an important role in tamoxifen resistance through lack of interaction with kinases that phosphorylate p27. In the suggested case of an increase oxidized state in the cell by chronic tamoxifen treatment, oxidized Trx is unable to reduce p27-affecting PTPs, which could play a role in the continued growth of cancer cells in the presence of tamoxifen treatment.…”
mentioning
confidence: 99%